(3GdeUHGM GdefjQ aj ZQjH GdTQM GdcHjQs - (3CMeO Hf eMeO Hf Ydj Gdajhej GdMehj, CHh GdYHGS,J (B770 (3g` s ((3eMeO aGd Hf SdjeGf s)
(3ChdgG (B:s
(3hHYO aEfi cfJ LeYJ cJGHkG ai ZQjH TQM GdhLjR GdQGaYi ` hChSYJ ajg aLQi di edd jfWhi Ndd, aCLHJ GNJUGQg , hSejJg (B" (3GdeUHGM GdefjQ ai ZQjH GdTQM GdcHjQ (B" (3cJGH GdGda eY GdHGA heG jKdKgeG s
(3BNQgG (B:s
(3hgPG eG hbY Ydjg GdGNJHGQ ef GdGNJUGQ GdeWhd , hcfJ LeYJ GdeWhd ef fMh JSYjf eUfakG aef Pdc GdJgPjH ddCRgQi s
(3HgG fXGe GdJYbjHIs
(3fSNI LjOI cJHJ dSjOi Hf GdeNJGQ Hf GdgjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B132s
Keywords: (3GddZIs